2019
DOI: 10.1177/1687814019872851
|View full text |Cite
|
Sign up to set email alerts
|

Research on spatial Lissajous trajectory vibrating screen

Abstract: Based on analyzing the problem of the screen with circular, linear, and elliptical trajectory, the spatial Lissajous trajectory has been put forward. The article analyzes the dynamic theory of the spatial Lissajous trajectory screen, and the virtual simulation with discrete-element method is applied to study the solid migration rules. A discrete-element model is developed based on the JKR contact model which takes into considerations viscous forces of contacting particles. Two important factors, migration velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Substituting Equation (22) into Equations ( 23) and (24), respectively, and simplifying, we can obtain…”
Section: Steady-state Responses Of the System Based On Ihbmmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting Equation (22) into Equations ( 23) and (24), respectively, and simplifying, we can obtain…”
Section: Steady-state Responses Of the System Based On Ihbmmentioning
confidence: 99%
“…They found that the influence of frequency on delamination and penetration rate was greater than that of swing angle. Lyu and Zhou 22 investigated the particle's movement rule of the vibrating screen with Lissajous spatial trajectory by DEM, which can effectively prevent the blockage of the screen hole. Safranyik et al 23 used the DEM to carry out the parameter optimization of the “Kertesz” screening machine produced in Hungary.…”
Section: Introductionmentioning
confidence: 99%
“…Using motors with excessive power reserves can adversely affect the power grid (significant reactive power) and increase the vibrating mass. In most cases, research on screens is limited to steady-state studies [15,18] and studies focused solely on the screening process using DEM simulations [19][20][21][22][23][24]. There are also attempts to develop vibration models that would consider the screened material's influence on the vibration parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers deal with the problem of the steady-state operation of screens and numerical simulation DEM to simulate the material's behaviour on the screening board [21][22][23][24][25]. Some researchers have also attempted to develop a vibration measurement model that considers material disturbances [26,27].…”
Section: Introductionmentioning
confidence: 99%